EFFECTIVENESS OF SPECIAL EDUCATION PROGRAMMES IN PRIMARY SCHOOLS: AN ANALYSIS OF THE LITERATURE - Firmansyah Firmansyah; Aslan Aslan (Adisam Publisher, 2025)
The effectiveness of special education programmes in primary schools, with a focus on the impact on the academic and social-emotional development of students with special needs. This study used a literature review method. The results showed that special education programs using inclusive approaches and personalised teaching contributed significantly to improved academic performance and student engagement. Effective collaboration between teachers, special education staff, parents and other professionals was also identified as an important factor in the success of the programmes. Nonetheless, the study highlighted implementation challenges, such as limited resources and the need for continuous professional development for educators. The conclusion of this analysis emphasises the need for increased investment and support in special education to overcome these challenges and ensure the achievement of optimal learning outcomes for all students.